The internationalisation of Chinese Television - Zhang, Hong (Javnost (Ljubljana), 2011)
This paper analyses the main features and power factors of the initial stage of television globalisation in mainland China. Based on document researches in three Chinese television stations of different administrative levels and in-depth interviews with television managers, producers and scholars, it argues that China's television was internationalised between 1978 and 1991. Television internationalisation was defined as a process driven by the partystate of adopting and reinventing the television cultural forms that were spreading internationally in order to build up national media and dominant ideologies in China. The argument is in three parts. I show first how the party-state relaxed its extreme anti-foreign stance in Chinese television as part of the national modernisation project within a modified party control system. Secondly, I show how these policies introduced international television flows and the transformation of some key aspects of television activities, in particular management practices, production values and program content. Thirdly, I show how the party state and its relations with Western states and international organisations were the primary influence on Chinese television, despite the rising influence of technologies, market forces and liberal intellectuals during the 1980s.
Keywords: Kitajska; mass media; množični mediji; television; televizija; vladni nadzor; svoboda govora; svoboda informiranja